Dostopni časi do pacientov z urgentnimi stanji v nujni medicinski pomoči Kočevje - Železnjak, Vladka (Obzornik zdravstvene nege, 2011)
Introduction: The response time in pre-hospital treatment of emergency patients is defined as the period between the time of the emergency call and the arrival of emergency medical services on scene of the incident which has a significant impact on the positive outcome of intervention. The established international standards mandate a 7 minute response time on emergency calls in urban areas and up to 14 minute response time in more remote or distanced regions in at least 90% of cases. Aim: The aim of the study was to analyse the emergency response times and assess them in relation to the recommended international standards. Methods: A quantitative research method was used to collect the data on random samples of all emergency interventions within a period of three months in 2009. The dispatch database, kept in the archives of the Emergency medical services Kočevje (EMSK) notes 80 emergency interventions within the period stated. The study analyses the distance from the EMSK (15 to 60 km) and the nearest hospital 60 to 120 km), the types of emergency and the emergency treatment outcomes. The anonymity of the patients was secured. The statistical analysis of the data was performed with the SPSS programme. A descriptive statistics was used for the measured variables - the one-sample t-test was used to identify statistically significant difference inresponse times in relation to the international standards and the independent samples t-test was employed to determine the relation between the mean response times and the patientsć survival. Results: Included in the studywere 67.7% of internal emergencies and 32.9% of traumas. In 75.9 % of cases, the patients were transported to definitive care, 16.5% of patients were appropriately treated on scene, in 6.3% the outcome was fatal and 1.3% of calls were false reports of emergencies. Results of the study show that in the majority of cases the mean response time to the distance of more than 15 km was 16.5 to 27.3 minutes with statistical dispersion 20.60. The one-sample t-test shows statistically significant differences in response times of EMSK in relation to the international standards (p=0.004). In emergencies with fatal outcomes the response time of EMSK was 12.0 13.5 minutes. Discussion and conclusions: Results of the study show that the mean response times to the scene of incident in the distance of more than 15.km from EMSK and 75 km from the nearest hospital exceeds the international standards by nearly 50%. Consequently, the emergency patients who should be treated within the first 14minutes have little or no chance of survival. One of the solutions in cases of cardiac arrest would be the use of automated defibrillators by laymen. The results obtained present a good basis for further study in the filed.
Keywords: nujna medicinska pomoč; nujne intervencije; odzivni čas; standardi